Analisis Transaksi Jizāf dalam Perspektif Qur’an dan Hadis - Maulidya Mora Matondang; Nawir Yuslem; M. Jamil (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Buying and selling activities are one aspect of muamalah which is very important in human life and receives great attention in the Qur'an and hadith. The principles of justice and honesty are the main foundation in every transaction, as illustrated in the verses which emphasize the importance of correct measures and scales, as in the words of Allah SWT: